1971
DOI: 10.4141/cjps71-080
|View full text |Cite
|
Sign up to set email alerts
|

Surface Pitting—a Storage Disorder of Sweet Cherries

Abstract: A storage disorder of sweet cherries referred the disorder than storage at a temperature to as surface pitting is described and illus-several deglees higher. Neither mineral foliar trated. Differeni handling, packaging and stor-sprays nor controlled atmosphere storage age treatments influenced the amount of the were effective in preventing surface pitting, disorder, but did not prevent it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 1 publication
3
26
1
Order By: Relevance
“…Wade and Bain (1980) mention surface pits to occur when cells in the hypodermis and first layer of mesocarp collapse. Literature defines two different types of pitting: the damage that occurs when enough pressure is applied gradually (compression), and the one that occurs instantaneously (impact) (Porritt et al, 1971;Facteau and Rowe, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Wade and Bain (1980) mention surface pits to occur when cells in the hypodermis and first layer of mesocarp collapse. Literature defines two different types of pitting: the damage that occurs when enough pressure is applied gradually (compression), and the one that occurs instantaneously (impact) (Porritt et al, 1971;Facteau and Rowe, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…However Facteau et al (1987) reported that there was no reduction of FSP as a result of CaCl 2 sprays. Warmer fruit that was handled or sent through packing lines developed less FSP than cooler fruit (Lidster and Tung 1980;Kupferman et al 1995;Porritt et al 1971). Thompson et al (1995) reported that shower-type hydrocoolers with high water drop heights cause FSP as does dropping cherries 25 cm on to a cleated conveyor belt.…”
mentioning
confidence: 99%
“…Mitcham et al (2002) describe FSP as an indentation in the surface of the fruit caused by the collapse of cells under the skin. The injury appears to occur during either the picking or sorting and packing processes and then develops in storage (Porritt et al 1971). Facteau and Rowe (1979) reported that percent soluble solids and fruit weight were negatively related to the amount of FSP in Lambert.…”
mentioning
confidence: 99%
See 2 more Smart Citations